Bleeding From Buried Cholecystogastrostomy Lumen-Apposing Metal Stent: The Double Pigtail Catheter Rescue Treatment. Issue 4 (24th April 2020) - Sánchez-Luna, Sergio A.; Wong, Morgan; Rustagi, Tarun
ABSTRACT: Lumen-apposing metal stents (LAMS) allow transmural drainage of the gallbladder for endoscopic management of acute cholecystitis in nonsurgical candidates. Delayed bleeding from cholecystogastrostomy or gallbladder after the LAMS placement has not been reported. There are no data for the replacement of LAMS with plastic stents to prevent recurrent delayed bleeding. We present a case to describe an alternative treatment approach for cholecystogastrostomy bleeding related to a buried LAMS.